Kinerja Karyawan PT XYZ Dilihat dari Lingkungan Kerja, Kepemimpinan dan Motivasi [Employee Performance of PT XYZ's Employees Observed from Work Environment, Leadership and Motivation] - Wibowo, Tri Sunu (Feedforward: Journal of Human Resource, 2023)
This study aims to determine the effect of 1) work environment on employee performance; 2) work environment on employee motivation; 3) leadership on employee performance; 4) leadership on employee motivation; 5) employee motivation on employee performance with the phenomenon of a decrease in customer rates as one of the benchmarks of employee performance. The research conducted was a quantitative research conducted at PT XYZ in DKI Jakarta using employees at the Directorate of Technology & Products as respondents in the research. Data collection was carried out using a questionnaire measuring tool using a Likert scale 1-5. The data analysis method used the Structural Equation Model (SEM) with SmartPLS software in processing the data. Work environment and leadership have a positive influence on employee motivation and both work environment, leadership and employee motivation have a positive influence on employee performance. This research relates to employee performance so that it can be used as material for consideration for organizations in an effort to improve employee performance and become a reference for further research.  Bahasa Indonesia Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh 1) lingkungan kerja terhadap kinerja karyawan; 2) lingkungan kerja terhadap motivasi karyawan; 3) kepemimpinan terhadap kinerja karyawan; 4) kepemimpinan terhadap motivasi karyawan; 5) motivasi karyawan terhadap kinerja karyawan dengan fenomena adanya peningkatan Churn Rate pelanggan sebagai salah satu acuan kinerja karyawan. Penelitian yang dilakukan merupakan penelitian kuantitatif yang dilakukan di PT XYZ yang berada di DKI Jakarta dengan menggunakan karyawan di Direktorat Teknologi & Produk sebagai responden dalam penelitian. Pengumpulan data dengan alat ukur kuesioner menggunakan skala Likert 1-5. Metode analisis data menggunakan Structural Equaition Model (SEM) dengan software SmartPLS dalam pengolahan datanya. Lingkungan kerja dan kepemimpinan memiliki pengaruh positif terhadap motivasi karyawan serta baik lingkungan kerja, kepemimpinan dan motivasi karyawan memberi pengaruh positif terhadap kinerja karyawan. Penelitian ini berhubungan dengan kinerja karyawan sehingga dapat dijadikan bahan pertimbangan bagi organisasi dalam upaya meningkatkan kinerja karyawan serta menjadi referensi untuk penelitian selanjutnya.